Concepts for a personal health record - Santos, Cândido (2014)
Healthcare is about information. It is usually assumed that personal health information exists primarily for professional's use but well informed patients motivate better informed professionals. A longitudinal health record containing a patient's medical history has been the holy grail of healthcare. Personal Electronic Health Records (P-EHR) hold the potential to transform healthcare by providing a complete set of patient managed information. We present a portable P-EHR's functionalities from the patient's perspective.